Knowledge and Attitude Regarding Mental Illness among People Residing in Selected Ward of Biratnagar - Karki, Ashmita; Chapagain, Sita; Dev, Oshan (Journal of Biratnagar Nursing Campus, 2023)
Introduction: For all people having a healthy mind, body, and social life is essential and intricately connected to one another. But in most of the countries mental health are given less importance than physical health. Due to the COVID-19 pandemic the number of people who suffer from anxiety and depressive illnesses greatly increased in 2020. Lack of public awareness is a potential barrier for the early detection, diagnosis and treatment of mental illness. This study was conducted with objective to assess knowledge and attitude regarding mental illness among people residing in selected ward of Biratnagar. Methods: Descriptive cross-sectional study design with probability sampling technique (simple random lottery method) was used to select ward out of 19 wards of Biratnagar and non-probability convenience sampling technique was used to select the sample which was 154. People who were critically ill and were unable to speak and hear at the time of data collection were excluded. Face to face interview using structured questionnaire was used for data collection. Data were analyzed by using descriptive as well as inferential statistics. Result: The study showed that 64.9% of respondents had good knowledge and 61.7% had favorable attitude towards mental illness. Finding showed association between community people’s knowledge about mental illness with their religion and educational status and their attitude with educational status. Conclusion: Majority of the respondents had good knowledge and attitude towards mental illness. Furthermore, the study found a statistically significant association between knowledge and religion, educational status, and attitude with educational status toward mental illness. To further increase knowledge and attitude regarding mental illness there is need of conducting awareness program among community people.